1992
DOI: 10.1111/j.1471-4159.1992.tb09387.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Insulin on Choline Acetyltransferase and Glutamic Acid Decarboxylase Activities in Neuron‐Rich Striatal Cultures

Abstract: We studied the effects of insulin, nerve growth factor (NGF), and tetrodotoxin (TTX) on cellular metabolism and the activity of glutamic acid decarboxylase (GAD) and choline acetyltransferase (ChAT) in neuron-rich cultures prepared from embryonic day 15 rat striatum. Insulin (5 micrograms/ml) increased glucose utilization, protein synthesis, and GAD activity in cultures plated over a range of cell densities (2,800-8,400 cells/mm2). TTX reduced GAD activity; NGF had no effect on GAD activity. Insulin treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 61 publications
0
17
0
3
Order By: Relevance
“…Cognitive function in hypertension has been found to be impaired in some 14 but not in all 5 ' 6 previous clinical studies. This population-based study confirmed that cognitive function is disturbed in elderly hypertensive subjects.…”
Section: I Normotentives I H Hypertens/normoins I B Hypertens/hyperinsmentioning
confidence: 91%
See 4 more Smart Citations
“…Cognitive function in hypertension has been found to be impaired in some 14 but not in all 5 ' 6 previous clinical studies. This population-based study confirmed that cognitive function is disturbed in elderly hypertensive subjects.…”
Section: I Normotentives I H Hypertens/normoins I B Hypertens/hyperinsmentioning
confidence: 91%
“…9 Although the association between essential hypertension and impaired cognitive function has previously been reported, 14 no studies have directly dealt with cognitive function in normoinsulinemic and hyperinsulinemic hypertensive subjects. Thus, the main result of the present study indicating that hyperinsulinemia identifies a subgroup of hypertensive subjects with a particularly poor cognitive function is a novel finding.…”
Section: I Normotentives I H Hypertens/normoins I B Hypertens/hyperinsmentioning
confidence: 99%
See 3 more Smart Citations